Plasmonic Modes in Thin Films: Quo Vadis? - Politano, Antonio; Chiarello, Gennaro (Frontiers in Materials, 2014)
Herein, we discuss the status and the prospect of plasmonic modes in thin films. Plasmons are collective longitudinal modes of charge fluctuation in metal samples excited by an external electric field. Surface plasmons (SPs) are waves that propagate along the surface of a conductor with applications in magneto-optic data storage, optics, microscopy, and catalysis. In thin films the electronic response is influenced by electron quantum confinement. Confined electrons modify the dynamical screening processes at the film/substrate interface by introducing novel properties with potential applications and, moreover, they affect both the dispersion relation of SP frequency and the damping processes of the SP. Recent calculations indicate the emergence of acoustic surface plasmons (ASP) in Ag thin films exhibiting quantum well states and in graphene films. The slope of the dispersion of ASP decreases with film thickness. We also discuss open issues in research on plasmonic modes in graphene/metal interfaes.